The mechanical modelling of nonhomogeneous reinforced structural systems by a coupled BEM formulation. (December 2019) - Neto, Antônio Rodrigues; Leonel, Edson Denner
Abstract: This study presents an accurate numerical formulation for the mechanical modelling of nonhomogeneous reinforced structures. Structural systems complex and efficient utilise such composition, which are largely observed in mechanical, naval and automotive industries, for instance. The Boundary Element Method (BEM) represents mechanically the plane nonhomogeneous domains in the formulation, in which viscous and time independent mechanical behaviours are accounted. The reinforcements are modelled by 1D truss elements, which are either represented by the Finite Element Method (FEM) or the BEM. The reinforcements allow for elastoplasticity behaviour. The 1D BEM approach leads to accurate and stable results in comparison with classical FEM modelling. The proposed formulation is applied in the mechanical analysis of four complex nonhomogeneous reinforced structural systems. The results achieved by the proposed formulation are compared against the responses of equivalent numerical models available in the literature. The accuracy, stability and robustness of the proposed formulation, particularly when domains and reinforcements are represented by the BEM, are illustrated.